Impact of Celebrities' Multiple Product Endorsements on Buyer's Attitude and Purchase Intentions - Pandey, Mrinalini (Indian Journal of Marketing, 2010)
Advertising can be considered as one of the most important and sometimes, the most expensive choices to be made by marketing managers when planning for communications campaigns as the expenditure on it requires justification. The main goal of advertising is to generate the sale of products by having consumers relate to messages and claims being made through different advertising mediums. Advertising that can arouse feelings, create liking, stir desire, or persuade convincingly can have a great impact on the consumer, generating sales for that product. The advertisers want to make their product distinct and so valuable that the consumer will become a repeat buyer. Since the consumers of today live in a media saturated and product cluttered environment, advertisers must be careful not to confuse the consumer. The greater the number of competing brands advertised in a product category, the greater is the likelihood that the target brand and its advertised attributes will be either confused with other product information or simply passed over. When multiple brands are advertised in a specific product category, overlapping themes might become confusing to the consumer, resulting in the consumers forming weak associations with the product and the advertisement.